2003
DOI: 10.1177/039139880302600407
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Expression in Tissue Engineered Cartilage of Aged Human Articular Chondrocytes in a Rotating Bioreactor

Abstract: This study describes the culture and three-dimensional assembly of aged human articular chondrocytes under controlled oxygenation and low shear stress in a rotating-wall vessel. Chondrocytes cultured in monolayer were released and placed without any scaffold as a single cell suspension in a rotating bioreactor for 12 weeks. Samples were analyzed with immunohistochemistry, molecular biology and electron microscopy. During serial monolayer cultures chondrocytes dedifferentiated to a “fibroblast-like” structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…It is difficult to meet these requirements with traditional static culture, whilst three-dimensional dynamic culture is able to accelerate cell proliferation and be conducive to chondrogenic differentiation and phenotype maintenance (7). Therefore, the present study applied bioreactor technology combined with microcarriers to rapidly amplify and induce chondrogenic differentiation in ADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to meet these requirements with traditional static culture, whilst three-dimensional dynamic culture is able to accelerate cell proliferation and be conducive to chondrogenic differentiation and phenotype maintenance (7). Therefore, the present study applied bioreactor technology combined with microcarriers to rapidly amplify and induce chondrogenic differentiation in ADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] More recently, Ohyabu et al 18 used rabbit bone marrow stromal cells in an RWV to produce cartilage tissue. Conza et al 19 showed that neocartilage cultivated on an RPM exhibits a much more regular distribution of cells within a well-developed cartilage extracellular matrix (ECM) than the layered structures produced under normal conditions without a supporting scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate bioreactor and mechanical stimuli may further improve the chondrogenic phenotype. 29 A similar 3D hydrogel, alginate-agarose, seeded with autologous articular chondrocytes, has recently been introduced into clinical work; excellent clinical, radiological, and histological results in the treatment of femoral condyle osteochondral lesions were demonstrated. 30 Relatively high ELS in the auricular chondrocytes revealed their capability to retain some characteristics of auricular cartilage tissue after 1 week in vitro culturing.…”
mentioning
confidence: 99%